Biofilm inspired fabrication of functional bacterial cellulose through ex-situ and in-situ approaches. (15th March 2023) - Gilmour, Katie A.; Aljannat, Mahab; Markwell, Christopher; James, Paul; Scott, Jane; Jiang, Yunhong; Torun, Hamdi; Dade-Robertson, Martyn; Zhang, Meng
Abstract: Bacterial cellulose (BC) has been explored for use in a range of applications including tissue engineering and textiles. BC can be produced from waste streams, but sustainable approaches are needed for functionalisation. To this end, BslA, a B. subtilis biofilm protein was produced recombinantly with and without a cellulose binding module (CBM) and the cell free extract was used to treat BC either ex-situ, through drip coating or in-situ, by incorporating during fermentation. The results showed that ex-situ modified BC increased the hydrophobicity and water contact angle reached 120°. In-situ experiments led to a BC film morphological change and mechanical testing demonstrated that addition of BslA with CBM resulted in a stronger, more elastic material. This study presents a nature inspired approach to functionalise BC using a biofilm hydrophobin, and we demonstrate that recombinant proteins could be effective and sustainable molecules for functionalisation of BC materials. Graphical abstract: Unlabelled Image